2014
DOI: 10.1136/heartjnl-2014-306916.49
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Type 2a Protein Phosphatases in Cardiac Health and Disease

Abstract: Cardiac physiology and hypertrophy are regulated by the phosphorylation status of many proteins, which is partly controlled by a poorly defined type 2A protein phosphatase-alpha4 intracellular signalling axis. Quantitative PCR analysis revealed that mRNA levels of the type 2A catalytic subunits were differentially expressed in H9c2 cardiomyocytes (PP2ACb [ PP2ACa [ PP4C [ PP6C), NRVM (PP2ACb [ PP2ACa = PP4C = PP6C), and adult rat ventricular myocytes (PP2ACa [ PP2ACb [ PP6C [ PP4C). Western analysis confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Nonetheless, the role of IMPDH2 in CAD has been poorly defined. The PPP4C gene encodes the PP4C protein, which is a member of the type 2 serine/threonine protein phosphatase family ( 46 ), and partly regulates the phosphorylation of numerous proteins implicated in cardiac physiology and hypertrophy ( 47 , 48 ). The present study indicated that IMPDH2 and PPP4C may be important genes in CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the role of IMPDH2 in CAD has been poorly defined. The PPP4C gene encodes the PP4C protein, which is a member of the type 2 serine/threonine protein phosphatase family ( 46 ), and partly regulates the phosphorylation of numerous proteins implicated in cardiac physiology and hypertrophy ( 47 , 48 ). The present study indicated that IMPDH2 and PPP4C may be important genes in CAD.…”
Section: Discussionmentioning
confidence: 99%